Positive discrimination and the question of fraternity: contrasting Ambedkar and Mandal on reservations - Gupta, Dipankar (1997)
The divergences between Ambedkar and Mandal on their respective reservation policies are significant. It is not just that Ambedkar's programme envisions the removal of untouchability and with it the undermining of the caste system in public life, but it is also about creating assets among those who have none. This is what brings the moral imperative of fraternity to the forefront. The assets of the better off are put in the collective pool so that socially valuable assets may be created in sites where there were none. This measure has a moral resonance, for out of this collective pooling new assets are being created. Reservations in the Mandal scheme lack this moral quality. The targeted beneficiaries of Mandal are quite plainly not without socially valuable assets. Further, they are unwilling to merge their existing tangible assets into the collective pool as their express purpose is to convert one kind of asset into another. Caste in the case of the Mandal Commission is an important political resource to be plumbed in perpetuity. The Mandal programme, therefore, is not in the spirit of enlarging fraternity, as the Ambedkar proposals are. - Reproduced
Keywords: Backward classes